Kompozicinės medžiagos vtrpesių energijos disipacija - Baradokas, Petras (Journal of Civil Engineering and Management, 1998)
Vibration energy dissipation of a composite material The paper discusses the problem of evaluating vibration energy dissipation of a composite material. It is suggested to express the dissipation cofficient in a line (2). The reduced component dissipation coefficients c i φi are the members of the line. The ratio of reduction ci , shows the proportion by which a separate component adds to the energy dissipation of the entire composition. By analysing the accumulated and dissipated strain energy of a composite material were obtained (6). On the basis of these expressions, formulas for calculating the dissipation coefficients of a three-layer bar and that with a galvanic covering were devised. The analysis made leads to the following conclusions: – the vibration energy dissipation coefficient of a composite material is equal to the sum of the reduced dissipation coefficients of the composition component materials; – the ratio of reduction c i depends on the value of the component accumulated energy; – for comparing separate components as to the energy dissipation, the product φi Ei should be used. Article in Lithuanian. First Published Online: 26 Jul 2012